Chemotherapy in Retinoblastoma: Current Approaches - Özge Yanık; Kaan Gündüz; Kıvılcım Yavuz; Nurdan Taçyıldız; Emel Ünal (Türk Oftalmoloji Dergisi, 2015)
Retinoblastoma (RB) is the most common childhood malignant intraocular tumor. Although enucleation and external beam radiotherapy have been historically used, today the most commonly used eye-sparing approach is chemotherapy. Chemotherapy can be used in both intraocular and extraocular RB cases. Chemotherapeutic agents may be applied in different ways, including systemic, subconjunctival, intra-arterial and intravitreal routes. The main purposes of application of systemic therapy are to reduce the tumor size for local treatment (chemoreduction), or to reduce the risk of metastasis after enucleation surgery (adjuvant therapy). Intra-arterial chemotherapy with the current name “super-selective intra-arterial infusion therapy” could be applied as primary therapy in tumors confined to the retina or as a secondary method in tumor recurrence. The most important advantage of intra-arterial therapy is the prevention of systemic chemotherapy complications. Intravitreal chemotherapy is administered in the presence of persistent or recurrent vitreous seeding. The term “extraocular RB” includes orbital invasion and metastatic disease. Current treatment for orbital invasion is neoadjuvant chemotherapy followed by surgical enucleation and adjuvant chemotherapy and radiotherapy after surgery. In metastatic disease, regional lymph node involvement, distant metastases, and/or central nervous system (CNS) involvement may occur. Among them, CNS involvement has the worst prognosis, remaining at almost 100% mortality. In metastatic disease, high-dose salvage chemotherapy and autologous hematopoietic stem cell rescue therapy are the possible treatment options; radiotherapy could also be added to the protocol according to the side of involvement.